EFFECT OF DIFFERENCE MECHANICAL FORCE INDUCTION TO OSTEOCLAST AND OSTEOBLAST HEAT SHOCK PROTEIN 25 EXPRESSION: EFEK PERBEDAAN INDUKSI KEKUATAN MEKANIS TERHADAP EKSPRESI HSP25 OSTEOKLAS DAN OSTEOBLAS - Muhammad Nurul Amin (Dentika: Dental Journal, 2012)
The usage of orthodontic appliance is to correct malocclusion involves alveolar bone remodeling. This process is stimulated by mechanical force which obtained from the activation orthodontic appliance. The force was used to depress teeth and the tissues surrounding it. This stress will become a signal to activate heat shock response yielding HSP synthesis. HSP25 plays a part in osteoclastic bone resorption and osteoblastic new bone forming. The aim of this study was to explore the change of osteoclast and osteoblast HSP25 expression in the different mechanical force induction at pressure and strain area. The subject was guinea pig (Cavia sp), divided into 2 groups. Control group did not use orthodontic appliance and treatment group was given mechanical force as 90 g, 120 g, and 150 g. Time usage of orthodontic appliance was 5 and 10 days. Osteoclast and osteoblast HSP25 were measured by counting cells after being conducted by immunohistochemistry method. The result showed that osteoclast HSP25 expression at pressure area on all groups had increased value compared to strain area and was different statistically. On the other hand, osteoblast HSP25 expression at strain area had increased value was compared to at pressure area and especially in group of 120 g and 10 days had difference statistically. In conclusion, different mechanical force induction could influence osteoclast and osteoblast HSP25 expression. HSP25 may represent one of the factors that influences osteoclast and osteoblast cellular activity and coupling process between osteoclast and osteoblast.